Effect of Storage Environment on the Extent of Lipid Oxidation in Peanut and Cowpea Based Infant Food - Bassey, F.I.; Mcwatters, K.H.; Edem, C.A.; Dosunmu, M.I.; E. Ebenso, Eno; Iwegbue, C.M.A. (Asian Journal of Chemistry, 2013)
The combined effect of storage temperature, relative humidity and available packaging materials on the lipid oxidative stability of peanut and cowpea based weaning food was investigated. Samples were prepared and stored in glass jars and polyethylene bags at 20, 30 and 40 ºC, respectively for 3 months. The zip-loc bag samples were stored at 75 % relative humidity to simulate the relative humidity in tropical regions of West Africa. The extent of lipid oxidation was measured via the level of hexanal liberation using automated head space solid-phase micro-extraction gas chromatography (auto HS-SPME-GC). It was observed that water vapor permeability of the polyethylene bag samples resulted in increased moisture content (from 4.42 to 7.80 %) and water activity (from 0.22 to 0.48) with storage-time and temperature. These increases were observed to adversely influence oxidative stability of the novel food as hexanal production increased from 5.45 to 13.794 ppm at 30 ºC in week 8 for sample stored in polyethylene bag. It was also observed that lipid oxidation was negligible within the first 8 weeks of storage for samples protected from moisture exchange (glass jar) at all storage temperatures as seen in the negligible levels of moisture content and water activity. Hexanal content of the glass jar samples was within the range of 5.45 and 33 ppm in the first 8 weeks. Results further showed that sample stored in glass jar at 40 ºC liberated the lowest level of hexanal (19.33 ppm) compared to values of 30.33 and 33 ppm liberated at 30 and 20 ºC, respectively at the end of 8 weeks. The weaning food stored in moisture barrier system can therefore be expected to achieve reasonable shelf stability within the desired short storage period without the extra cost of antioxidants.